Success of tumorsphere isolation from WHO grade IV gliomas does not correlate with the weight of fresh tumor specimens: an immunohistochemical characterization of tumorsphere differentiation. Issue 1 (December 2016) - Sung, Kyoung; Shim, Jin-Kyoung; Lee, Ji-Hyun; Kim, Se; Park, Sohee; Roh, Tae-Hoon; Moon, Ju; Kim, Eui-Hyun; Kim, Sun; Lee, Su; Huh, Yong; Kang, Seok-Gu; et al.
Abstract Background A trend of stage-by-stage increase in tumorsphere (TS) formation from glioma samples has been reported. Despite this trend, not all surgical specimens give rise to TSs, even World Health Organization (WHO) grade IV gliomas. Furthermore, it has been reported that differences in overall survival of primary glioblastoma patients depends on the propensity of their tumors to form TSs. However, the weights of fresh specimens vary from one surgical isolate to the next. Methods Accordingly, we evaluated the relationship between the weights of surgical specimens in WHO grade IV gliomas with the capacity to isolate TSs. Thirty-five fresh WHO grade IV glioma specimens were separated into two groups, based on whether they were positive or negative for TS isolation, and the relationship between TS isolation and weight of surgical specimens was assessed. Results We observed no significant difference in the weights of surgical samples in the two groups, and found that the optimal weight of specimens for TSs isolation was 500 mg. Conclusion Thus, contrary to our expectations, the ability to isolate TSs from WHO grade IV glioma specimens was not related to the weight of fresh specimens.